Scaling site-specific fertilizer advisories in Ethiopia: Innovation use and practice - Mesfin, Tewodros; Ebrahim, Mohammed; Abera, Wuletawu (2025)
This report documents the innovation use and practice of the Localized Agronomy and Fertilizer Advisory system within Ethiopia’s Harmonized Digital Fertilizer and Agronomic Solutions (LAFA/HaFAS) framework in 2025. It examines how site-specific fertilizer recommendations are translated from validated research into operational delivery through public and private pathways. Evidence is drawn from large-scale piloting by the National Agricultural Research System, digital advisory delivery through FarmerChat, bundled advisory–finance–insurance services implemented by LERSHA, and public-sector implementation through Farmer–Research–Extension (FRE) linkages and Client Feedback Mechanisms under the Ministry of Agriculture. More than 1,430 geo-referenced on-farm piloting trials and substantial user engagement with digital advisory services highlight both adoption potential and delivery constraints. The findings show that effective scaling depends on institutional coordination, governance, timely delivery, and feedback mechanisms, in addition to agronomic accuracy. Overall, the report demonstrates that LAFA/HaFAS has advanced from a technical innovation to an operational, nationally embedded advisory system, providing outcome-level evidence to support responsible scaling of site-specific fertilizer advisories in Ethiopia